Where are the Women on the whole Scene of Art? - Terpesheva, Dobromira (Sledva : NBU Journal of Humanities and Arts, 2019)
The text offers an analysis of the role of women in art and society today and poses fundamental questions regarding the visibility of female artists in Bulgaria. This study was created in connection with the Women's Artistic Projects Fund, a project of the Bulgarian Women's Fund. The fund aims to act against the under-representation of women in the professional arts and the cultural sector, to give visibility to the creativity of female artists and to increase their access to financial resources.